HUBUNGAN PEMANFAATAN TRUST PETANI DENGAN PERILAKU USAHATANI PADI SAWAH DI KECAMATAN BATANG ASAM KABUPATEN TANJUNG JABUNG BARAT - Rendra, Rendra (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This study aims to increase the attention of various parties on the importance of trust in social capital owned by the farming community, especially rice farmers and in the future it is hoped that a model can be developed in developing social capital as a potential and strategy for empowering farming communities. In the short term it is expected to know and identify the value of trust in the social capital owned and how much trust is owned by the farming community and to find out how it relates to the farm’s behavior. The method used is to use a combination of qualitative (descriptive) and quantitative methods. The research data were obtained from the results of observations and interviews with structured interviews using questionnaires. The data obtained will be processed statistically using Chi-Square analysis. This research was conducted in half a year or in one wetland rice planting season. This research will be very useful for the government and private sector as well as NGOs’ who are directly involved in carrying out community empowerment activities. For academics is also an important point in the development of social capital for improving the welfare of the farming community in the future. Keywords: trust and behavior of rice farming